Secure payment parking system (SPS) with Excel database software / Syed Luqman Putra Syed Putra Zainol Alam - Syed Putra Zainol Alam, Syed Luqman Putra (2024)
Car parking systems play a vital role in managing the increasing demand for parking spaces in urban areas. According to statistical data, the number of vehicles on the roads has been steadily increasing, leading to overcrowded parking lots and time-consuming parking procedures. To amidst this situation, "Secure Payment Parking System (SPS) with Excel Software Database System" is built. This project addresses the need for an efficient and secure car parking solution, leveraging ESP32 and ESP32 CAM modules, infrared sensors, LEDs, and a custom mobile application developed with MIT App Inventor. The problem statement underscores the challenges associated with conventional parking systems, including traffic delays and inconvenient payment system such queuing at the payment counter. In response to the limitations of traditional gate-based parking systems, the project introduces a “one-way step entry” approach. The focus of this project are to streamline the parking experience and enhance security. Also this project can develop an intelligent online parking payment system that allows users to conveniently check-in using QR code thus making online payment and exit the system with an exit gateway verification code. The project benefits include a more efficient parking process, reduced user waiting times, secure payment processing, and enhanced user experience. Future recommendations may involve expanding the system to include additional payment options, integrating with smart city infrastructure, and incorporating machine learning algorithms for predictive parking availability.